1963
DOI: 10.1002/ange.19630752103
|View full text |Cite
|
Sign up to set email alerts
|

Die basenkatalysierte Umsetzung von Ketonen mit Schwefelwasserstoff

Abstract: descofaktors ist imeinzelnen nicht bekannt. AusderTatsache, sowie durch Tetrahydrobiopte-rin ersetzt werden kann, darf man schliekn, daR es sich um ein 6-substituiertes Tetrahydropterin handelt. Da das bei der Hydroxylierung entstehende partiell hydrierte Pteridin-Derivat [320] weder ein 5.8-noch ein 7.8-und sehr wahrscheinlich auch kein 5.6-Dihydropterin sein kann, durfte ein Redox-System mit den Komponenten (165) und (166) vorliegen. H Mit diesem ersten Beispiel fur die Cofaktor-Rolle eines einfachen unkonj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
3

Year Published

1964
1964
1990
1990

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 15 publications
0
17
0
3
Order By: Relevance
“…Therefore, possible reaction mechanisms of the proposed pyrite-pulled carbon dioxide fixation remain obscure. It should, however, be remembered that hydrogen sulfide (or even better, the SH-anion) is highly nucleophitic and that Mayer et al (1963) demonstrated a reduction of a carbonyl group to a methylene group by the oxidation of hydrogen sulfide to elemental sulfur to occur with vicinal diketones but not with less reactive monoketones. The reaction may be assumed to produceed via the disulfide anion (Sf-).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, possible reaction mechanisms of the proposed pyrite-pulled carbon dioxide fixation remain obscure. It should, however, be remembered that hydrogen sulfide (or even better, the SH-anion) is highly nucleophitic and that Mayer et al (1963) demonstrated a reduction of a carbonyl group to a methylene group by the oxidation of hydrogen sulfide to elemental sulfur to occur with vicinal diketones but not with less reactive monoketones. The reaction may be assumed to produceed via the disulfide anion (Sf-).…”
Section: Introductionmentioning
confidence: 99%
“…Eine saurekatalysierte Dithiol-Bildung ist iibrigens bereits friiher erwahnt [40], aber erst wesentlich spa-b) Mit basischen K a t a l y s a t o r e n Die Bildung der geminalen Dithiole (7) ist auch im basischen Medium auljerordentlich begunstigt [57]. Wir konnten fur diese interessante Verbindungsklasse eine einfache, allgemeine und sehr ergiebige Synthese ausarbeiten, nach der Ketone bei 0 bis 20°C mit Schwefelwasserstoff in Gegenwart von Aminen in einem polaren Losungsmittel umgesetzt werden [58].…”
Section: Ausunclassified
“…Dagegen fallen beim Cycloheptanon, Methj lcyclohexylketon und einigen anderen Ketonen in ma-Diger Ausbeute auch Thioketone an [57,60]. Ob diese als Primar-oder Sekundarprodukte zu werten sind, lie0 sich bisher nicht entscheiden.…”
Section: Ausunclassified
See 1 more Smart Citation
“…We have now found that simple u-isocyanoalkanoic esters can be alkylated through their derivatives anionized at the u position, to yield higher a-isocyanoalkanoic acids that can be hydrolyzed to amino acids. Table) can be obtained from ethyl isocyanoacetate (I) and 2 equivalents of alkylating agent ( 5 ) in the presence of a base such as potassium tert-butoxide or sodium hydride in tetrahydrofuran or ether/DMSO. As a curiosity it may be mentioned that both 1,2-dibromoethane and 2-chloroethyl p-toluenesulfonate react with ( I ) undergoing ring closure to ethyl 1 -isocyanocycIopropanecarboxylate (10) .…”
mentioning
confidence: 99%